2021
DOI: 10.1088/1748-9326/ac1815
|View full text |Cite
|
Sign up to set email alerts
|

Albedo-induced global warming impact of Conservation Reserve Program grasslands converted to annual and perennial bioenergy crops

Abstract: Climate benefit assessments of bioenergy crops often focus on biogeochemical impacts, paying little if any attention to biogeophysical impacts. However, land conversions required for large-scale bioenergy crop production are substantial and may directly affect the climate by altering surface energy balance. In the US, such land conversions are likely to be met in part by converting Conservation Reserve Program (CRP) grassland to bioenergy crops. Here, we converted three 22 year old CRP smooth brome grass field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In line with other studies [55], the largest contribution to the overall total seasonal GWI ∆α came from the non-growing season months, during which all the cover types exhibited cooling effects that varied in magnitude depending on the ecoregion. Once again, urban was the only cover type that contributed to warming effects in the growing season, generally following a decreasing trend going from June to September.…”
Section: Seasonal Percent Contributions To the Total Cooling And Warmingsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with other studies [55], the largest contribution to the overall total seasonal GWI ∆α came from the non-growing season months, during which all the cover types exhibited cooling effects that varied in magnitude depending on the ecoregion. Once again, urban was the only cover type that contributed to warming effects in the growing season, generally following a decreasing trend going from June to September.…”
Section: Seasonal Percent Contributions To the Total Cooling And Warmingsupporting
confidence: 91%
“…Analyzing land transformation with reference to forests is only one method. For example, other studies and policymakers have focused on land transformation in the context of bioenergy conversions [55] and land management practices to compare landscape dynamics to agriculture [65][66][67].…”
Section: Assumptions and Limitations Of The Studymentioning
confidence: 99%
“…Similarly, Sciusco et al (2020) and Sciusco et al (2022), who integrated spatial and temporal changes as main drivers of albedo variations, showed that cropland had higher albedo and intra-annual variabilities, with an average RF between −5.6 W m −2 to −1.2 W m −2 when compared to forests. Abraha et al (2021) also assessed the biogeophysical climate impact of albedo using multiple modeled conversions from an unconverted reference CRP grassland using radiation measures from eddy covariance towers, which showed that switchgrass and restored prairie fields provided albedo-induced cooling.…”
Section: Crop Conversion From Maizementioning
confidence: 99%
“…Previous studies on albedo‐induced warming effects are mostly based on satellite data (Fang et al, 2007; Sciusco et al, 2020, 2022; Zhang et al, 2010), while biophysical models (Cherubini et al, 2012; Smith et al, 2020) and ground surface measurements (Abraha et al, 2021; Miller et al, 2016) have been lacking. Within the latter studies, measurements have been restricted to the effects of albedo on only one to two bioenergy crop species, over very short periods that do not thoroughly inform longer temporal changes, through the use of remote sensing that can potentially miss entire portions of the growing season, or through modeling studies that may be oversimplified and not reflect realistic changes seen on the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…The above-ground biomass of a bioenergy crop is burned after harvesting for energy and, if below-ground biomass increases carbon accumulated in the soil, there is a net removal of CO 2 from the atmosphere (Anderson-Teixeira and DeLucia, 2011). Crops and grasses, including perennial bioenergy crops such as Miscanthus x giganteus and switchgrass (Panicum virgatum), also have higher albedo values than forests (Bonan, 2008;Miller et al, 2016;Abraha et al, 2021). The direct effect of the higher albedo of perennial bioenergy crops on the atmospheric radiation balance can be large.…”
Section: Introductionmentioning
confidence: 99%